Zabytkowa kamienica przy ul. Sienkiewicza 21 w Łodzi - Klemantowicz, Dariusz (Zeszyty Wiejskie, 2016)
In the city center of Lodz, on the corner of 21, Henryk Sienkiewicz street (formerly Wild, Mikołajewska) and 10, Stanislaw Moniuszko street (formerly Passage Meyer) there is a historic town house. Since 1990 it had been the property of the University of Lodz. Until recently it housed the Germanic philology. A few years ago the Department of German was transferred to the newly constructed building of the Faculty of Philology at the University of Lodz at 171/173, Pomorska street. The first owner of the building was Louis Meyer (1841–1911), a well-known industrialist of German origin at the end of the nineteenth century. He was one of approx. 30 Lodz millionaires. A few years before World War I Solomon Danziger (1858–1938) purchased the property of the Jewish faith industrialist, and during the Second World War it became the property of the Germans. It is currently owned by the University of Lodz.